N-Oxalylglycine-Conjugated Hyaluronic Acid as a Macromolecular Prodrug for Therapeutic Angiogenesis - Andrew H. DeMaria; Jeoung Soo Lee; Ken Webb (Gels)
Hypoxia-inducible factor-1α (HIF-1α) initiates the cellular response to low oxygen levels, making it an attractive target for stimulating therapeutic angiogenesis. Several small molecules have been identified that stabilize HIF-1α and activate the angiogenic signaling pathway. However, achieving therapeutic doses of bioactive small molecules in target tissues remains challenging. In this paper, we report the synthesis and characterization of a new macromolecular prodrug composed of the pro-angiogenic small molecule N-oxalylglycine conjugated to hyaluronic acid (HA-NOG). NOG was conjugated to HA by esterification, and release was significantly increased in the presence of degradative enzymes, esterase and hyaluronidase, compared to physiological buffer, confirming that the release of NOG is primarily enzymatically driven. Normal human dermal fibroblasts (NHDFs) cultured with HA-NOG exhibited HIF-1α accumulation in the cell nucleus and dose-dependent increases in mRNA expression levels of three direct HIF transcriptional targets. Conditioned medium from these cells stimulated endothelial cell tubulogenesis. As an initial evaluation of safety and possible side effects, HA-NOG was found not to significantly affect NHDF metabolic activity, proliferation, or collagen deposition. These studies demonstrate that HA-NOG releases NOG in response to cellular enzymatic activity, activating the HIF signaling pathway and culminating in the secretion of soluble factors that activate endothelial cells without adversely affecting other cellular metabolic pathways.